2004
DOI: 10.1176/appi.ajp.161.4.670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parental Alcohol and Drug Disorders on Adolescent Personality

Abstract: In contrast to findings in some adult samples, personality characteristics associated with a family history of substance use disorders are found even in adolescent offspring who have not yet developed these disorders themselves, suggesting that personality might be one indicator of familial risk for substance use disorders during this developmental stage. Personality profiles of offspring of parents with substance use disorders also show some diagnostic specificity, with constraint associated with parental dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 35 publications
4
62
1
Order By: Relevance
“…This is also very much the case in the wider research literature, in which adolescents are now risk carriers of their own, likely to manifest problems of drug use (Obot et al, 2001), negative personality traits (Elkins et al, 2004), and other risk behaviour or problematised characteristics. Risk becomes a pathogenic trait, rather than, for instance, a response to a particular set of circumstances.…”
Section: The Risk Gradient: Framing Young People As Risk Takers and Pmentioning
confidence: 88%
“…This is also very much the case in the wider research literature, in which adolescents are now risk carriers of their own, likely to manifest problems of drug use (Obot et al, 2001), negative personality traits (Elkins et al, 2004), and other risk behaviour or problematised characteristics. Risk becomes a pathogenic trait, rather than, for instance, a response to a particular set of circumstances.…”
Section: The Risk Gradient: Framing Young People As Risk Takers and Pmentioning
confidence: 88%
“…McGue and colleagues (1997; found that alcohol dependence is particularly common among individuals who have high levels of both behavioral disinhibition and negative emotionality and that alcohol dependence is primarily associated with negative emotionality, while illicit drug use disorders are primarily associated with constraint (McGue, Slutske, & Iacono, 1999;McGue, Slutske, Taylor, & Iacono, 1997). Similarly, Elkins et al (2004) found that adolescent offspring of parents with a history of alcohol dependence scored significantly higher on negative emotionality than adolescents with no parental history of alcohol dependence, and negative emotionality did not differ for offspring of parents with and without a drug abuse/dependence history (Elkins, McGue, Malone, & Iacono, 2004). They found that this pattern characterized both offspring with an SUD and those who had not yet developed an SUD, which supports negative emotionality as an indicator of familial risk for alcoholism.…”
Section: General Ne Liability: Link Between Alcohol Use Disorder and mentioning
confidence: 99%
“…Personality variables have been shown to distinguish between FH+ and FHÀ groups, suggesting that certain personality traits may serve as markers of a person's risk for development of a substance abuse problem (Elkins et al, 2004). Personality variables measuring behavioral disinhibition and negative emotionality are often associated with substance abuse (Sher et al, 1999).…”
Section: Introductionmentioning
confidence: 99%